Penanganan Simpang tak Bersinya: Studi Jalan Simpang Haji Rais Kota Tangerang Selatan - Kusuma, Heris Cahya; Tjahjani, AR Indra; Naibaho, Pio Ranap Tua (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The intersection of Jalan H. Rais is where 3 (three) roads meet, namely Jalan H. Jamat Gang Rais, Jalan Puspitek Segment 1, and Jalan Puspitek Segment 2. This intersection often experiences long queues due to inadequate intersection capacity so that it cannot accommodate the volume of vehicles during morning and evening rush hours. The research method used was a direct survey method at the research location to collect traffic data at the H. Rais intersection and the surrounding roads. The research results found that the average length of the queue before handling during peak hours on weekdays was 168.52 m and delays were 35,471 with an intersection service level (LOS) D, while the average length of the queue before handling during peak hours on holidays was 119 .82 m and a delay of 33.52 with a level of service (LOS) D. H. Rais intersection performance for the next 5 years, before handling becomes worse with the result that the average queue length during weekday peak hours is 219, 64 m and a delay of 49,137 with an intersection service level (LOS) E, while the average queue length during holiday peak hours is 218.28 m and a delay of 43,635 with an intersection service level (LOS) E. Handling that needs to be done at the intersection H. Rais road in short-term scenario 1 is by providing road equipment facilities and assignment of traffic officers, and in short-term scenario 2 by widening the bend radius to a minimum of 7.8 m and widening the H. Jamat Gang Rais road to 6 m, while The treatment carried out at the H. Rais intersection in the long term is to change the Puspitek road type to 4/2-T with a width of 6 m per direction.